2021
DOI: 10.3389/fmicb.2021.702467
|View full text |Cite
|
Sign up to set email alerts
|

Fungi Associated With Woody Tissues of European Beech and Their Impact on Tree Health

Abstract: Filamentous fungi associated with woody tissues of European Beech (Fagus sylvatica) and isolated from diseased trees and healthy trees were examined in relation to their impact on tree health. To this end, classical culture-based isolation methods, in planta inoculations and fungal identification using ITS-barcode and morphological characters were used. Stem endophytes of healthy beech saplings collected in German forests were isolated to determine endophyte communities in woody stem tissues. Pathogenicity tes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(16 citation statements)
references
References 55 publications
2
14
0
Order By: Relevance
“…In our study, we observed strong enrichment of Hypoxylon fragiforme only in discolored wood areas of sample D2 and it was almost absence (detected 8 times) in nondiscolored wood areas of the same beech tree (ND2). We also detected Neonectria coccinea in the sample D2 which confirms that Hypoxylon fragiforme has the potential to co-occur with Neonectria coccinea [40].…”
Section: Resultssupporting
confidence: 70%
See 4 more Smart Citations
“…In our study, we observed strong enrichment of Hypoxylon fragiforme only in discolored wood areas of sample D2 and it was almost absence (detected 8 times) in nondiscolored wood areas of the same beech tree (ND2). We also detected Neonectria coccinea in the sample D2 which confirms that Hypoxylon fragiforme has the potential to co-occur with Neonectria coccinea [40].…”
Section: Resultssupporting
confidence: 70%
“…Hypoxylon fragiforme is even classified as a latent invader within the xylem of European beech [47]. Hypoxylon fragiforme is reported to co-occur with Neonectria coccinea [40]. In our study, we observed strong enrichment of Hypoxylon fragiforme only in discolored wood areas of sample D2 and it was almost absence (detected 8 times) in nondiscolored wood areas of the same beech tree (ND2).…”
Section: Resultssupporting
confidence: 48%
See 3 more Smart Citations